UNSUR-UNSUR ISYARY DALAM SEBUAH TAFSIR NUSANTARA (Telaah Analitis Tafsir Faid al-Rahman Kiai Sholeh Darat) - Faiqoh, Lilik (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2018)
This research discusses about the elements of isyary in a Tafsir Nusantara: Analitical study of Tafsir Faid al-Rahman created by Kiai Sholeh Darat. Kiai Sholeh Darat is a figure of ulama? tasawuf who emerged in the end of 19th century that made tafsir creation which used Javanese lamguage (Arabic pegon). Seem that there is isyary nuance when interpreting al-Qur?an verse. The elements of isyary in interpretation can enrich the treasure of Tafsir Nusantara. In this research, there are three important problems related on the theme above, the first is the elements of isyary in Kiai Sholeh Darat?s interpretation. The second is which are the examples of isyary?s elements that is included in tafsir Faid al-Rahman. And the third, what is the contribution and the relevance in treasure of tafsir Nusantara. With using historical approach and the methodology of tafsir, it will be explained that in a creation of tafsir Nusantara has nuance of isyary?s elements when Kiai Sholeh Darat interpreted al-Qur?an verses. Exactly, this interpretation can?t be separated from his own mufasir that has influence of the characters of sufi in his writings. So, this research can be concluded, the first in interpreting there are the elements of isyary, it seems when interpreting al-Qur?an verse with the nuance of isyary or sufi. The second, displayed the examples with nuance of isyary and socio-cultural, for the example about damage of earth, faith, and praying. The third, the contribution can give riches of color or tafsir style and the solution included when there are social problems in archipelago, like there is road repairing, opening the job, and so on.